A low-temperature, high-efficiency, porcelain-forming, flame-retardant powder and its preparation method and application

The low-temperature and high-efficiency porcelain flame retardant powder prepared by the sol-gel method is combined with the polymer, which solves the problems of high temperature and low strength of existing silicone rubber materials, and achieves the effect of efficient porcelain forming at low temperatures and providing effective protection under high temperature environments.

CN115926254BActive Publication Date: 2025-04-29BENGBU ESTONE POLYMER COMPOSITES CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211705789.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-29
Publication Date
2025-04-29
Estimated Expiration
2042-12-29

AI Technical Summary

Technical Problem

Existing silicone rubber-based polymer composite materials have high porcelain formation temperatures and low porcelain formation strengths at low temperatures, making it difficult to provide effective protection in high temperature or flame environments.

Method used

Low-temperature and high-efficiency porcelain flame retardant powder is prepared by sol-gel method, including silicates and calcium, aluminum, and silicon inorganic compounds deposited on the surface of silicates, and is compounded with polymers to form a high-strength and structurally complete ceramic layer.

Benefits of technology

A high-strength ceramic layer is formed at around 400°C, which is resistant to high temperatures of 1500°C, and has good flame retardant properties, which is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115926254B_ABST
    Figure CN115926254B_ABST
Patent Text Reader

Abstract

The present invention discloses a low-temperature, high-efficiency, ceramic-forming flame-retardant powder and its preparation method and application, which relates to the technical field of inorganic ceramic flame-retardant powder materials. The low-temperature, high-efficiency, ceramic-forming flame-retardant powder of the present invention comprises silicate and inorganic compounds of calcium, aluminum and silicon deposited on the surface of silicate; and the low-temperature, high-efficiency, ceramic-forming flame-retardant powder is applied to the preparation of ceramic flame-retardant composite materials. The new composite material formed by the low-temperature, high-efficiency, ceramic-forming flame-retardant powder prepared by the present invention and a polymer can form a high-strength and structurally complete ceramic layer at about 400°C, can withstand high temperatures of 1500°C, and has good flame-retardant properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention relates to the technical field of inorganic ceramic flame-retardant powder materials, and in particular to a low-temperature, high-efficiency ceramic-forming flame-retardant powder and a preparation method and application thereof. Background technology:

[0002] With the development of science and technology, new requirements are constantly being put forward for high temperature resistant, fire resistant, fireproof and ablative materials in many fields. On the one hand, it is necessary to form a ceramic shell at a lower temperature to support and protect the normal operation of internal devices; on the other hand, it is necessary to resist the impact and ablation of high temperature or flame at a higher temperature to ensure that the equipment and devices are not damaged. Therefore, the preparation of low-temperature and high-efficiency ceramic powder materials and the development of new thermal runaway and high-temperature resistant composite materials formed by their combination with organic matter are particularly important.

[0003] A class of polymer composite materials represented by ceramic silicone rubber is a new type of heat-resistant protective material. It has excellent mechanical properties and corrosion resistance of polymers at room temperature, and can form a self-supporting ceramic body in high temperature environment or fire situation, thereby preventing flames, heat and air from spreading into the material, inhibiting the diffusion of flammable gases formed by polymer decomposition into the flame layer, and achieving the effect of flame retardancy, fire prevention and heat insulation. However, the ceramic forming temperature of ordinary silicone rubber is high and the ceramic forming strength is low. At the same time, the structural integrity of the ceramic protective layer formed is poor, and it is difficult to play the best protective role. Therefore, the market needs a protective material that can be ceramicized at low temperature and high efficiency and can be used in conjunction with polymer materials to achieve better high temperature or flame protection performance. Summary of the invention:

[0004] The technical problem to be solved by the present invention is to provide a low-temperature, high-efficiency, ceramic-forming flame-retardant powder and a preparation method thereof. The new composite material formed by the powder and a polymer material can form a high-strength ceramic layer at about 400°C. As the temperature increases, the ceramic strength increases accordingly, and the ceramic structure can remain intact, resistant to high temperatures of 1500°C, and at the same time has excellent flame retardant properties.

[0005] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:

[0006] One of the purposes of the present invention is to provide a low-temperature, high-efficiency, porcelain-forming, flame-retardant powder, comprising silicate and inorganic compounds of calcium, aluminum and silicon deposited on the surface of the silicate.

[0007] The second object of the present invention is to provide a method for preparing a low-temperature, high-efficiency, porcelain-forming flame-retardant powder, using a sol-gel method, comprising the following steps:

[0008] (1) dissolving a calcium source in a first solvent to prepare a solution A;

[0009] (2) dissolving the aluminum source in a second solvent to form a solution or sol B;

[0010] (3) dissolving the silicon source in a third solvent to form a solution or sol C;

[0011] (4) dissolving silicate in a fourth solvent to prepare a silicate slurry;

[0012] (5) Adding silicate slurry, solution A, solution or sol B, and solution or sol C into a reaction kettle, adding a precipitant, stirring, washing, drying, and crushing, and surface-modifying the obtained powder with a surfactant to obtain a porcelain-forming flame-retardant powder.

[0013] The third object of the present invention is to provide a low-temperature, high-efficiency, ceramic-forming, flame-retardant powder obtained according to the aforementioned preparation method.

[0014] A fourth object of the present invention is to provide a ceramic flame-retardant composite material, comprising a polymer and the aforementioned low-temperature, high-efficiency ceramic flame-retardant powder.

[0015] The fifth object of the present invention is to provide the application of the aforementioned ceramic flame-retardant composite material in technical fields such as aerospace, new energy, wires and cables, building materials, decorative materials, electronic appliances, information and transportation.

[0016] The beneficial effects of the present invention are as follows: the new composite material formed by the low-temperature, high-efficiency, ceramic-forming flame-retardant powder prepared by the present invention and a polymer can form a high-strength and structurally complete ceramic layer at about 400°C, can withstand high temperatures of 1500°C, and has good flame-retardant properties; in addition, the preparation method of the low-temperature, high-efficiency, ceramic-forming flame-retardant powder is simple and easy, has good repeatability, and is suitable for industrial production. Description of the drawings:

[0017] Figure 1 is the SEM image of the raw material wollastonite;

[0018] Figure 2 This is a SEM image of the porcelain-forming flame-retardant powder A prepared in Example 1;

[0019] Figure 3 This is a SEM image of the porcelain-forming flame-retardant powder B prepared in Example 2;

[0020] Figure 4 This is a SEM image of the porcelain-forming flame-retardant powder C prepared in Example 3;

[0021] Figure 5 This is the SEM image of the porcelain-forming flame-retardant powder D prepared in Example 4. Specific implementation method:

[0022] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments and diagrams.

[0023] The invention provides a low-temperature high-efficiency porcelain-forming flame-retardant powder, comprising silicate and inorganic compounds of calcium, aluminum and silicon deposited on the surface of the silicate.

[0024] The present invention also provides a method for preparing a low-temperature, high-efficiency, porcelain-forming, flame-retardant powder, which adopts a sol-gel method and comprises the following steps:

[0025] (1) dissolving a calcium source in a first solvent to prepare a solution A;

[0026] (2) dissolving the aluminum source in a second solvent to form a solution or sol B;

[0027] (3) dissolving the silicon source in a third solvent to form a solution or sol C;

[0028] (4) dissolving silicate in a fourth solvent to prepare a silicate slurry;

[0029] (5) Adding silicate slurry, solution A, solution or sol B, and solution or sol C into a reaction kettle, adding a precipitant, stirring, washing, drying, and crushing, and surface-modifying the obtained powder with a surfactant to obtain a porcelain-forming flame-retardant powder.

[0030] Preferably, the silicate is at least one of albite, potassium feldspar, wollastonite, mica, talc, and attapulgite, and more preferably wollastonite.

[0031] Preferably, the calcium source is at least one of calcium carbonate, calcium bicarbonate, calcium nitrate, calcium hypochlorite and calcium oxide, more preferably calcium bicarbonate.

[0032] Preferably, the aluminum source is at least one of boehmite, aluminum nitrate, aluminum hydroxide, and aluminum sol, and more preferably aluminum sol.

[0033] Preferably, the silicon source is at least one of tetraethyl orthosilicate and silica sol, and more preferably silica sol.

[0034] Preferably, the first solvent, the second solvent, the third solvent and the fourth solvent are water or a mixed solvent consisting of water and an organic solvent, more preferably water.

[0035] Preferably, the surfactant is at least one of γ-methacryloxypropyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane and stearic acid; the added amount of the surfactant is 0.5-2% of the mass of the powder.

[0036] More preferably, the surfactant is γ-methacryloxypropyltrimethoxysilane, and the added amount is 1% of the mass of the powder.

[0037] Preferably, the mass ratio of the calcium source, aluminum source and silicon source is (1-4):(1-4):(3-9), the calcium source is calculated as calcium oxide, the aluminum source is calculated as aluminum oxide, and the silicon source is calculated as silicon dioxide.

[0038] Preferably, the total coating amount of the calcium source, aluminum source and silicon source in the porcelain-forming flame-retardant powder is 1-30%, more preferably 5-15%, the calcium source is calculated as calcium oxide, the aluminum source is calculated as alumina, and the silicon source is calculated as silicon dioxide.

[0039] Preferably, the precipitant is ammonia water or a combination of ammonia water and one of ammonium carbonate, sodium carbonate and potassium carbonate. When the calcium source is calcium bicarbonate, ammonia water is added to generate calcium carbonate precipitation; when the calcium source is calcium nitrate and the aluminum source is aluminum nitrate, ammonium carbonate, sodium carbonate or potassium carbonate is added to generate calcium carbonate precipitation, and then ammonia water is added to generate aluminum hydroxide precipitation; another function of ammonia water is to change the surface charge of silicon dioxide, destroy the stability of the system, and cause the silica sol to precipitate.

[0040] Preferably, the stirring temperature is 40-80° C. and the stirring time is 1-3 h.

[0041] The present invention also provides a low-temperature, high-efficiency, porcelain-forming, flame-retardant powder obtained according to the aforementioned preparation method.

[0042] The present invention also provides a ceramic composite material, comprising a polymer and the aforementioned low-temperature, high-efficiency, ceramic-forming, flame-retardant powder.

[0043] Preferably, the polymer is at least one of polyvinyl chloride, chlorinated polyethylene, chlorosulfonated polyethylene, silicone rubber, fluorosilicone rubber, ethylene propylene rubber, natural rubber, polyisoprene rubber, styrene-butadiene rubber, butadiene rubber, butyl rubber, nitrile rubber, chloroprene rubber, epichlorohydrin rubber, fluororubber, perfluoroether rubber, polyolefin, polyphenylene ether resin, polyamide resin, polycarbonate, epoxy resin, polyurethane, acrylic resin, polyacrylonitrile resin, polyvinyl alcohol resin, bismaleimide resin, and cyanate ester resin, and more preferably methyl vinyl silicone rubber.

[0044] Preferably, the low-temperature high-efficiency ceramic powder is added in an amount of 5 to 70% in the ceramic flame-retardant composite material.

[0045] The present invention also provides applications of the aforementioned ceramic flame-retardant composite material in technical fields such as aerospace, new energy, wires and cables, building materials, decorative materials, electronic appliances, information and transportation.

[0046] The technical solution of the present invention is described in detail below through specific embodiments:

[0047] Example 1

[0048] 1. Dissolve calcium bicarbonate in water to prepare solution A1 with a concentration of 3 g / mL;

[0049] 2. Dissolve wollastonite in water to prepare a wollastonite aqueous slurry with a solid content of 50%;

[0050] 3. Add 2000g of wollastonite aqueous slurry, 10mL of solution A1, 50g of aluminum sol with a solid content of 20%, and 100g of silica sol with a solid content of 30% into the reactor in turn, adjust the pH to 9.3 with 25% ammonia water, stir at 75°C for 1h, wash, dry and crush the obtained powder, and dry-modify it with 1% γ-mercaptopropyltrimethoxysilane to obtain porcelain-forming flame-retardant powder A.

[0051] 4. By mass percentage, put 50% methyl vinyl silica gel and 50% porcelain powder A into a kneader, mix and stir for 60 minutes under vacuum conditions at 130°C, release the pressure, take out the rubber, and after the rubber is cooled to room temperature, mix it evenly with DCBP (bis (2,4-dichlorobenzoyl) peroxide) accounting for 1% of the mass of the rubber on an open mill, put the rubber into a flat-plate vulcanizer for compression molding, the vulcanization pressure of the flat-plate vulcanizer is 15 MPa, and the vulcanization conditions are 120°C×10 min, to obtain a 150mm×150mm×2mm sample.

[0052] Comparative Example 1

[0053] By mass percentage, 50% methyl vinyl silica gel, 46.5% wollastonite, 0.5% alumina, 1.5% silicon dioxide, 0.5% calcium oxide, and 1% γ-mercaptopropyl trimethoxysilane were all put into a kneader, mixed and stirred for 60 minutes under vacuum conditions at 130°C, the pressure was released, and the rubber was taken out. After the rubber was cooled to room temperature, the rubber was mixed evenly with DCBP (bis-2,4-dichloroperoxybenzoyl) accounting for 1% of the rubber mass on an open mill, and the rubber was placed in a flat vulcanizer for compression molding. The vulcanization pressure of the flat vulcanizer was 15MPa, and the vulcanization conditions were 120°C×10min, and a 150mm×150mm×2mm sample was obtained. .

[0054] Example 2

[0055] 1. Dissolve calcium bicarbonate in water to prepare solution A2 with a concentration of 3 g / mL;

[0056] 2. Dissolve wollastonite in water to prepare a wollastonite aqueous slurry with a solid content of 50%;

[0057] 3. Add 2000g of wollastonite aqueous slurry, 20mL of solution A2, 100g of aluminum sol with a solid content of 20%, and 200g of silica sol with a solid content of 30% into the reactor in turn, adjust the pH to 9.3 with 25% ammonia water, stir at 75°C for 1h, wash, dry and crush the obtained powder, and dry-modify it with 1% γ-methacryloxypropyltrimethoxysilane to obtain porcelain-forming flame-retardant powder B.

[0058] 4. By mass percentage, put 50% methyl vinyl silica gel and 50% porcelain powder B into a kneader, mix and stir for 60 minutes under vacuum conditions at 130°C, release the pressure, take out the rubber, and after the rubber is cooled to room temperature, mix it evenly with DCBP (bis-2,4-dichlorobenzoyl peroxide) accounting for 1% of the mass of the rubber on an open mill, put the rubber into a flat-plate vulcanizer for compression molding, the vulcanization pressure of the flat-plate vulcanizer is 15MPa, and the vulcanization conditions are 120°C×10min, and a 150mm×150mm×2mm sample is obtained.

[0059] Example 3

[0060] 1. Dissolve calcium nitrate in water to prepare solution A3 with a concentration of 1 g / mL;

[0061] 2. Dissolve aluminum nitrate in water to prepare solution B3 with a concentration of 1 g / mL;

[0062] 3. Dissolve wollastonite in water to prepare a wollastonite aqueous slurry with a solid content of 50%;

[0063] 4. Add 2000g of wollastonite aqueous slurry, 70mL of solution A3, 84mL of solution B3, and 200g of silica sol with a solid content of 30% into the reactor in sequence, add 45g of ammonium carbonate, stir at 40°C for 1h to react with calcium nitrate to form calcium carbonate precipitate, then add excess 25% ammonia water and stir for 1h to react with aluminum nitrate to produce aluminum hydroxide precipitate, wash, dry, and crush the obtained powder, and dry-modify it with 1% γ-methacryloxypropyltrimethoxysilane to obtain porcelain-forming flame-retardant powder C.

[0064] 5. By mass percentage, put 50% methyl vinyl silica gel and 50% porcelain powder C into a kneader, mix and stir for 60 minutes under vacuum conditions at 130°C, release the pressure, take out the rubber, and after the rubber is cooled to room temperature, mix it evenly with DCBP (bis (2,4-dichlorobenzoyl) peroxide) accounting for 1% of the mass of the rubber on an open mill, put the rubber into a flat-plate vulcanizer for compression molding, the vulcanization pressure of the flat-plate vulcanizer is 15MPa, and the vulcanization conditions are 120°C×10min, and a 150mm×150mm×2mm sample is obtained.

[0065] Comparative Example 2

[0066] By mass percentage, 50% methyl vinyl silica gel, 43.8% wollastonite, 1.1% calcium oxide, 3% silicon dioxide, 1.1% aluminum oxide, and 1% γ-methacryloxypropyltrimethoxysilane were all put into a kneader, mixed and stirred for 60 minutes under vacuum conditions at 130°C, the pressure was released, and the rubber material was taken out. After the rubber material was cooled to room temperature, the rubber material was evenly mixed with DCBP (bis-2,4-dichloroperoxybenzoyl) accounting for 1% of the mass of the rubber material on an open mill, and the rubber material was placed in a flat vulcanizer for compression molding. The vulcanization pressure of the flat vulcanizer was 15MPa, and the vulcanization conditions were 120°C×10min, and a 150mm×150mm×2mm sample was obtained.

[0067] Example 4

[0068] 1. Dissolve calcium nitrate in water to prepare solution A5 with a concentration of 3 g / mL;

[0069] 2. Dissolve aluminum nitrate in water to prepare solution B5 with a concentration of 3 g / mL;

[0070] 3. Dissolve wollastonite in water to prepare a wollastonite aqueous slurry with a solid content of 50%;

[0071] 4. Add 2000g of wollastonite aqueous slurry, 70mL of solution A5, 84mL of solution B5, and 600g of silica sol with a solid content of 30% into the reactor in sequence, add 135g of ammonium carbonate, stir at 40°C for 1h to react with calcium nitrate to form calcium carbonate precipitate, then add excess 25% ammonia water and stir for 1h to react with aluminum nitrate to produce aluminum hydroxide precipitate, wash, dry, and crush the obtained powder, and dry-modify it with 2% γ-mercaptopropyltrimethoxysilane to obtain porcelain-forming flame-retardant powder D.

[0072] 4. By mass percentage, put 50% methyl vinyl silica gel and 50% porcelain powder E into a kneader, mix and stir for 60 minutes under vacuum conditions at 130°C, release the pressure, take out the rubber, and after the rubber is cooled to room temperature, mix it evenly with DCBP (bis-2,4-dichlorobenzoyl peroxide) accounting for 1% of the mass of the rubber on an open mill, put the rubber into a flat-plate vulcanizer for compression molding, the vulcanization pressure of the flat-plate vulcanizer is 15MPa, and the vulcanization conditions are 120°C×10min, and a 150mm×150mm×2mm sample is obtained.

[0073] Comparative Example 3

[0074] By mass percentage, 50% methyl vinyl silica gel, 35.4% wollastonite, 3.3% calcium oxide, 6% silicon dioxide, 3.3% aluminum oxide, and 2% γ-methacryloxypropyltrimethoxysilane were all put into a kneader, mixed and stirred for 60 minutes under vacuum conditions at 130°C, the pressure was released, and the rubber material was taken out. After the rubber material was cooled to room temperature, the rubber material was evenly mixed with DCBP (bis-2,4-dichloroperoxybenzoyl) accounting for 1% of the mass of the rubber material on an open mill, and the rubber material was placed in a flat vulcanizer for compression molding. The vulcanization pressure of the flat vulcanizer was 15MPa, and the vulcanization conditions were 120°C×10min, and a 150mm×150mm×2mm sample was obtained.

[0075] Example 5

[0076] 1. Dissolve calcium nitrate in water to prepare solution A4 with a concentration of 1 g / mL;

[0077] 2. Dissolve aluminum nitrate in water to prepare solution B4 with a concentration of 1 g / mL;

[0078] 3. Dissolve the attapulgite in water to prepare an aqueous attapulgite slurry having a solid content of 50%;

[0079] 3. Add 2000g of attapulgite aqueous slurry, 70mL of solution A4, 84mL of solution B4, and 200g of silica sol with a solid content of 30% into the reactor in sequence, and add 45g of ammonium carbonate. Stir at 40°C for 1h to react with calcium nitrate to form calcium carbonate precipitate. Add excess 25% ammonia water and stir for 1h to react with aluminum nitrate to produce aluminum hydroxide precipitate. Wash, dry, and crush the obtained powder. Use 1% γ-methacryloxypropyltrimethoxysilane for dry modification to obtain porcelain-forming flame-retardant powder E.

[0080] 4. By mass percentage, put 50% methyl vinyl silica gel and 50% porcelain powder D into a kneader, mix and stir for 60 minutes under vacuum conditions at 130°C, release the pressure, take out the rubber, and after the rubber is cooled to room temperature, mix it evenly with DCBP (bis-2,4-dichloroperoxybenzoyl) accounting for 1% of the mass of the rubber on an open mill, put the rubber into a flat-plate vulcanizer for compression molding, the vulcanization pressure of the flat-plate vulcanizer is 15MPa, and the vulcanization conditions are 120°C×10min, and a 150mm×150mm×2mm sample is obtained.

[0081] The particle size and specific surface area of ​​the porcelain-forming flame-retardant powder prepared in the above embodiment were tested. The results are shown in Table 1.

[0082] Table 1

[0083]

[0084] From Table 1 and Figure 1-5It can be judged that after the inorganic compound is coated on the surface of silicate, the particle size of the powder increases and the specific surface area increases significantly. The possible reason is that the surface is coated with more small particles, with sizes ranging from submicron to nanometer. Figure 5 Especially obvious.

[0085] Comparative Example 4

[0086] In terms of mass percentage, 50% methyl vinyl silica gel, 43.8% attapulgite, 1.1% calcium oxide, 3% silicon dioxide, 1.1% aluminum oxide, and 1% γ-methacryloxypropyltrimethoxysilane were all put into a kneader, mixed and stirred for 60 minutes under vacuum conditions at 130°C, the pressure was released, and the rubber material was taken out. After the rubber material was cooled to room temperature, the rubber material was evenly mixed with DCBP (bis-2,4-dichloroperoxybenzoyl) accounting for 1% of the mass of the rubber material on an open mill, and the rubber material was placed in a flat vulcanizer for compression molding. The vulcanization pressure of the flat vulcanizer was 15 MPa, and the vulcanization conditions were 120°C×10min to obtain a 150mm×150mm×2mm sample.

[0087] The performance tests were performed on the samples prepared in the above examples and comparative examples, and the results are shown in Table 2.

[0088] Flame retardant grade test: reference standard GB / T 10707-2008.

[0089] Tensile strength test: reference standard GB / T 528-2009.

[0090] Elongation at break test: Reference standard GB / T 528-2009.

[0091] Bending strength test: Reference standard GB / T 6569-2006, sintering conditions are 400℃×45min.

[0092] Ceramic body integrity test: 1500℃ flame burning for 5 to 10 minutes.

[0093] Table 2

[0094]

[0095] It can be seen from Table 2 that the ceramic flame-retardant polymers prepared in Examples 1-5 can reach a ceramic strength of more than 17 MPa after being kept at 400°C for 45 minutes; and can form a structurally complete ceramic body by ablation at 1500°C for 5 to 10 minutes.

[0096] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A low-temperature, high-efficiency, porcelain-forming, flame-retardant powder, comprising silicate and inorganic compounds of calcium, aluminum and silicon deposited on the surface of the silicate; The preparation of the low-temperature high-efficiency porcelain-forming flame-retardant powder adopts a sol-gel method, comprising the following steps: (1) dissolving a calcium source in a first solvent to prepare a solution A; (2) dissolving an aluminum source in a second solvent to form a solution or sol B; (3) dissolving the silicon source in a third solvent to form a solution or sol C; (4) dissolving silicate in a fourth solvent to prepare a silicate slurry; (5) Adding silicate slurry, solution A, solution or sol B, and solution or sol C into a reaction kettle, adding a precipitant, stirring, washing, drying, and crushing, and surface-modifying the obtained powder with a surfactant to obtain a porcelain-forming flame-retardant powder.

2. The low-temperature, high-efficiency, porcelain-forming, flame-retardant powder according to claim 1, characterized in that: The silicate is at least one of albite, potassium feldspar, wollastonite, mica, talc, and attapulgite; The calcium source is at least one of calcium carbonate, calcium bicarbonate, calcium nitrate, calcium hypochlorite and calcium oxide; The aluminum source is at least one of boehmite, aluminum nitrate, aluminum hydroxide, and aluminum sol; The silicon source is at least one of tetraethyl orthosilicate and silica sol; The mass ratio of the calcium source, the aluminum source, and the silicon source is (1-4): (1-4): (3-9), the calcium source is calculated as calcium oxide, the aluminum source is calculated as aluminum oxide, and the silicon source is calculated as silicon dioxide; The total coating amount of the calcium source, aluminum source and silicon source in the porcelain-forming flame-retardant powder is 1-30%, the calcium source is calculated as calcium oxide, the aluminum source is calculated as aluminum oxide, and the silicon source is calculated as silicon dioxide.

3. The low-temperature, high-efficiency, porcelain-forming, flame-retardant powder according to claim 1, characterized in that: The first solvent, the second solvent, the third solvent and the fourth solvent are water or a mixed solvent consisting of water and an organic solvent.

4. The low-temperature, high-efficiency, porcelain-forming, flame-retardant powder according to claim 1, characterized in that: The surfactant is at least one of γ-methacryloxypropyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane and stearic acid; the added amount of the surfactant is 0.5-2% of the mass of the powder.

5. The low-temperature, high-efficiency, porcelain-forming, flame-retardant powder according to claim 1, characterized in that: The precipitant is ammonia water or a combination of ammonia water and one of ammonium carbonate, sodium carbonate and potassium carbonate; The stirring temperature is 40-80°C and the stirring time is 1-3h.

6. A ceramic flame-retardant composite material, characterized in that: The ceramic flame-retardant composite material comprises a polymer and the low-temperature, high-efficiency ceramic flame-retardant powder according to any one of claims 1 to 5.

7. The ceramic flame-retardant composite material according to claim 6, characterized in that: The polymer is at least one of polyvinyl chloride, chlorinated polyethylene, chlorosulfonated polyethylene, silicone rubber, fluorosilicone rubber, ethylene propylene rubber, natural rubber, polyisoprene rubber, styrene-butadiene rubber, butadiene rubber, butyl rubber, nitrile rubber, chloroprene rubber, epichlorohydrin rubber, fluororubber, perfluoroether rubber, polyolefin, polyphenylene ether resin, polyamide resin, polycarbonate, epoxy resin, polyurethane, acrylic resin, polyacrylonitrile resin, polyvinyl alcohol resin, bismaleimide resin, and cyanate ester resin.

8. The ceramic flame-retardant composite material according to claim 6, characterized in that: The addition amount of the low-temperature high-efficiency ceramic-forming flame-retardant powder in the ceramic composite material is 5-70%.

9. Application of the ceramic flame-retardant composite material according to claim 7 or 8 in aerospace, new energy, wires and cables, building materials, decorative materials, electronic appliances, information and transportation.

Citation Information

Patent Citations

  • Ceramic fire-resistant functional filling material as well as preparation method and purpose thereof

    CN107501946A